2019
DOI: 10.5195/ledger.2019.178
|View full text |Cite
|
Sign up to set email alerts
|

A Blockchain Enhanced Framework for Social Networking

Abstract: Social networking sites have given users unprecedented opportunities for the generation and dissemination of content. A variety of social networking sites exist for different purposes, to afford users a range of anonymous and non-anonymous options for self-expression, and the ability to be a part of a virtual community. These “affordances” enable users to create and share content; however, the ability to partially or wholly detach user identity from the content has resulted in unique challenges for content acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Shi et al (2020) analyzed existing problems in the collaborative management of Humanities and Social Sciences thematic databases, investigated the applicability of blockchain in this context, and constructed a blockchain model for the collaborative management of databases and related tasks. Finally, Murimi (2019) proposed a secure and reliable blockchain social framework to protect the value of user-generated content, aiming to solve the problem of partial or complete separation of user identity information and shared content in social networks.…”
Section: Online Knowledge Sharing In Blockchainsmentioning
confidence: 99%
“…Shi et al (2020) analyzed existing problems in the collaborative management of Humanities and Social Sciences thematic databases, investigated the applicability of blockchain in this context, and constructed a blockchain model for the collaborative management of databases and related tasks. Finally, Murimi (2019) proposed a secure and reliable blockchain social framework to protect the value of user-generated content, aiming to solve the problem of partial or complete separation of user identity information and shared content in social networks.…”
Section: Online Knowledge Sharing In Blockchainsmentioning
confidence: 99%
“…Proposed Model [45] Model based on security data storage [53] Solution to managing the privacy preferences of a user [55] Autonomous decentralized online social network architecture [59] Blockchain-based data mining methodology [60] A blockchain-based privacy-preserving framework (BPP) [62] An auditable and trustworthy access control structure [65] A hierarchical blockchain-based attribute matching system [68] BCOSN, a blockchain-based Online Social Network [70] A decentralized social networking architecture [71] A blockchain-based model for data storage [76] An autonomous resource request transaction framework [80] Blockchain-enhanced version of social networking (BEV-SNSs) [81] Blockchain-based identity providers [82] A decentralized social network based on Ethereum and IPFS [83] RPchain, a blockchain based academic social networking platform [84] A protocol and authentication with a blockchain algorithm [86] Ushare: a blockchain scheme for social networks Similar to the models proposed for detecting fake content, the models proposed for protecting data use Blockchain-based elements such as smart contracts and consensus algorithms. Dawei Xu et al [45] recommended a novel truthfulness information storing system, CL-BC (Clark-Wilson), which contains a theoretical strategy, initial setting architecture, and comprehensive flux architecture to construct the entree regulator structure of a distributed veracity information storing system and optimize the safety of risks such as over-agreement and illegitimate completion in the storing of information.…”
Section: Referencementioning
confidence: 99%
“…The structure allows community groups to distribute articles via smart contract by offering a motivating network. Renita M. Murimi [80] introduced a system providing users with control of access to information and value creation via social network site dealings named BEV-SNS (blockchain-enhanced version of social networking sites). Karl Pinter et al [81] utilized a blockchain-based identity approach to boost safety and availability, and proposed the blockchain to improve the safety and accessibility of e-government facilities such as e-ID.…”
Section: Referencementioning
confidence: 99%
“…In particular, they store the content in a Merkle tree i.e., a binary tree built using hash pointers. In another work, Murimi [12] proposed Blockchain Enhanced Framework for Social Networking (BEV-SNS), a framework for incentivizing user behavior on SNSs to achieve two objectives: control over data access, and creation of value through SNS transactions. To illustrate this framework, author provides examples with SNSs that lie along the spectrum of anonymity and showed that the framework could be scaled for future use in a variety of collocated spaces.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the research has focused on using various artificial intelligence [13] or machine learning [1,3,7] algorithms for curbing the issue. Distributed ledger technologies and specifically blockchain, also provides opportunities that can help in combating the fake news [11,12,15]. These technologies enable privacy, security, and trust in a peer-to-peer network in a decentralized fashion without any central managing authority [6].…”
mentioning
confidence: 99%